IMPLEMENTASI METODE JOB SAFETY ANALYSIS SEBAGAI UPAYA PENCEGAHAN KECELAKAAN KERJA PADA KARYAWAN: (Studi pada PKS Rantau Kasai PT. Tor Ganda Kandir Medan) - Tinambunan, Rapima Sartika; Safrin, Feby Aulia (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This study aims to analyze the Job Safety Analysis method as an effort to prevent work accidents at Rantau Kasai PKS. The goal is to determine whether the application of this method has been carried out correctly and has created safe and comfortable conditions. The study utilizes a qualitative method to describe the phenomena that occur. Data collection techniques include interviews, observation, and documentation. The study collects information by interviewing key informants, main informants, and additional informants. The data analysis technique involves a data reduction process, data presentation, and discussion. The conclusion of the study indicates that the application of the Job Safety Analysis method at Rantau Kasai PKS has been implemented quite well. Each stage of the work is observed, potential hazards are identified through socialization and notifications, and control measures are implemented. These measures include placing boundary marks on areas deemed hazardous and displaying safety signs as warnings.